2012
DOI: 10.3892/mmr.2015.3408
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of isoflurane pretreatment in rats with focal cerebral ischemia and the underlying molecular mechanism

Abstract: Abstract. Inflammation and immunity are important in the pathogenesis of cerebral ischemia. Toll-like receptor 4 (TLR4) is involved in the inflammatory responses of injured brain tissues. Emerging studies have focused on the effect of isoflurane (ISO) pretreatment on cerebral ischemia, however, the association between ISO pretreatment and TLR4 during cerebral ischemia remains to be elucidated. In the present study, the protective role of ISO pretreatment in rats with focal cerebral ischemia reperfusion was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Both ketamine and isoflurane have been reported to impact neuro-inflammation, with acute and long-lasting effects (Lockwood et al, 1993;Miyazaki et al, 1997;Wu et al, 2008;Xiang et al, 2014;Xiao et al, 2015;Zhao et al, 2011). Further, changes in glutamate, GABA, and calcium ++ oscillation signaling have been reported after isoflurane anesthesia (Miyazaki et al, 1997;Xiang et al, 2014;Zhao et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Both ketamine and isoflurane have been reported to impact neuro-inflammation, with acute and long-lasting effects (Lockwood et al, 1993;Miyazaki et al, 1997;Wu et al, 2008;Xiang et al, 2014;Xiao et al, 2015;Zhao et al, 2011). Further, changes in glutamate, GABA, and calcium ++ oscillation signaling have been reported after isoflurane anesthesia (Miyazaki et al, 1997;Xiang et al, 2014;Zhao et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, isoflurane may transiently hamper the progression and delay the onset of cerebral infarct 26. In addition, isoflurane pretreatment reduces neurological deficits, brain edema, and cerebral infarct size after ischemia/reperfusion 11. We determined in the previous study that isoflurane post-treatment has a protective effect on tPA-exaggerated brain injury 1; however, the protective mechanisms of isoflurane against tPA-induced injury after ischemic insult were not elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…Many experimental studies have demonstrated that isoflurane provides protective effects in many organs after ischemic reperfusion injury 8-10. Isoflurane pretreatment reduced neurological deficits, brain edema, and infarction volume in ischemic animal model 11. Furthermore, isoflurane preconditioning attenuates inflammation and injury by decreasing pro-apoptotic factors and increasing anti-apoptotic factors 12.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Toll-like receptor 4 (TLR4) is expressed primarily in microglia151617. We and other studies have reported that TLR4 can induce microglial activation and cytokine production in brain injury, trauma and neurodegenerative diseases1819. Moreover, Hara et al reported that TLR4 knockout (KO) mice had significantly smaller infarct volumes and better neurobehavioural recovery at 24 h after I/R injury compared with wild-type mice.…”
mentioning
confidence: 99%